Budget planning in the public sector colleges, state Zulia. - Ferrer, Evelyn (Frónesis)
The aim was to analyze the budget planning at the University Institutes public sector, Zulia state. The authors were Bateman and Snell (2005), Burbano (2005), among others. The research was descriptive and field transeccional non-experimental design. The population were the Public Sector University Institutes of Zulia state. a survey of (15) items was used and obtained a reliability of 0.91. It was concluded that present weaknesses the object of study University Institutes, when defining the objective, policies for a given fiscal period, serving the budget as an instrument to this planning process to estimate the amounts that will be needed to run to take these actions to practice, in turn obtaining program resources.